Pseudomyogenic (epithelioid sarcoma-like) hemangioendothelioma of bone: Clinicopathologic features of 5 cases - Kösemehmetoğlu, Kemal; Relchi, Bharat; Wakely, Paul E., Jr.; Pant, Vinita; Dervişoğlu, Sergülen; Aydıngöz, Üstün (W.B. Saunders, 2019)
Pseudomyogenic hemangioendothelioma (PHE) is an uncommon mesenchymal tumor of intermediate malignant potential with characteristic clinicopathologic and genetic features. Although bone involvement accompanies nearly one-fourth of reported cases of soft tissue PHEs, primary intraosseous PHE is rare. Herein, we report five cases of primary intraosseous PHEs. Male to female ratio was 4:1, with an average age of 28 years (age range, 5–44 years). Radiologically, tumors presented as lytic lesions in the proximal femur (two), diaphysis of the tibia (one), distal radius (one) and vertebrae (one). Multifocal lesions were observed in four cases. Histopathologic examination revealed plump spindle cells and prominent nucleoli. New bone formation was noted in three cases. Immunohistochemically, all tumors were positive for CD31 and negative for CD34. Pan Cytokeratin (CK) (AE1/3) was positively expressed in all, except a single tumor, in which CK7 and Cam5.2 were expressed. INI1/SMARCB1 was completely retained in all tumors. A single patient underwent surgical resection. During follow-up, two cases showed no evidence of disease within two and five years, respectively. Differential diagnosis of a PHE of bone includes osteoblastoma, epithelioid angiosarcoma, metastatic carcinoma, metastatic rhabdomyosarcoma, and epithelioid sarcoma. Caution must be exercised as pan CK (AE1/3) might not be expressed; therefore, the use of other cytokeratins, such as Cam5.2 is recommended. Awareness of such an entity in bone is the key to the diagnosis.
Keywords: Bone Tumor; Epithelioid Sarcoma-Like Hemangioendothelioma; Pseudomyogenic Hemangioendothelioma